Soluble Receptor Potentiates Receptor-Independent Infection by Murine Coronavirus - Taguchi, Fumihiro (American Society for Microbiology, 2002)
Mouse hepatitis virus (MHV) infection spreads from MHV-infected DBT cells, which express the MHV receptor CEACAM1 (MHVR), to BHK cells, which are devoid of the receptor, by intercellular membrane fusion (MHVR-independent fusion). This mode of infection is a property of wild-type (wt) JHMV cl-2 virus but is not seen in cultures infected with the mutant virus JHMV srr7. In this study, we show that soluble MHVR (soMHVR) potentiates MHVR-independent fusion in JHMV srr7-infected cultures. Thus, in the presence of soMHVR, JHMV srr7-infected DBT cells overlaid onto BHK cells induce BHK cell syncytia and the spread of JHMV srr7 infection. This does not occur in the absence of soMHVR. soMHVR also enhanced wt virus MHVR-independent fusion. These effects were dependent on the concentration of soMHVR in the culture and were specifically blocked by the anti-MHVR monoclonal antibody CC1. Together with these observations, direct binding of soMHVR to the virus spike (S) glycoprotein as revealed by coimmunoprecipitation demonstrated that the effect is mediated by the binding of soMHVR to the S protein. Furthermore, fusion of BHK cells expressing the JHMV srr7 S protein was also induced by soMHVR. These results indicated that the binding of soMHVR to the S protein expressed on the DBT cell surface potentiates the fusion of MHV-infected DBT cells with nonpermissive BHK cells. We conclude that the binding of soMHVR to the S protein converts the S protein to a fusion-active form competent to mediate cell-cell fusion, in a fashion similar to the fusion of virus and cell membranes.